Demographic Factors Influencing Skilled Birth Attendance in Sudurpashchim (Siddhajyoti Interdisciplinary Journal, 2026)
The maternal mortality is a key challenge to the state of global health as a significant number of women continue to give birth without professional care. Skilled birth attendance (SBA) is an effective program that can be used to curb maternal and neonatal mortality. Inequality within the socio-demographic and economic groups still exists despite advances. The cross-sectional study was based on data on 262 women aged 15-49 years in Sudurpashchim Province, Nepal, and had a live birth within five years before the survey, using data of the 2022 Nepal Demographic and Health Survey (NDHS). Determinants SBA were analyzed through descriptive and binary logistic regression. Findings indicated more SBA use among younger, educated, urban and rich women. Regression analysis indicated that maternal age (30 -49 years), higher education, and lower birth order were some of the important predictors. The women that had three or more births were less likely to access skilled care. The study concludes that education and parity are major factors that determine the use of SBA. Specific measures based on targeting multiparous and less-educated women are required. Development of female education and community outreach should be culturally sensitive on the female health results in the marginalized regions.